Qualitative Analysis of the Concept of Tabdzir in the Qur'an: A Study of Al-Azhar Tafsir and Its Contribution to Good Asset Management - Ummu Lathifah; Andri Nirwana; Muhammad Zakir Husein (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
This research is entitled